Alternatives to gas flaring: a multi-criteria decision approach applied to a case study in Russia. Issue 3 (3rd May 2016) - Colombo, E.; Barbieri, J.; Brambilla, M.
Abstract : During recent years, the issue of gas flaring has become an increasingly relevant problem for the international community. The claim to more sustainable development offers a renewed prospective in the observation of gas flaring and emphasizes that recovering the associated gas could induce economic, environmental and social benefit. The true core of the issue, as is widely accepted, is not a lack of appropriate technologies, but in the number of criteria involved, which makes it difficult to identify a list of alternatives and connecting all the involved stakeholders in the negotiation process. The complexity of this problem can be mitigated using a decision-making method. The objective of the present work is to identify and formulate a supportive decision system based on the Analytic Hierarchy Process. Application of the model to a real case underlines the strengths and weaknesses of the model, leading to the conclusion that a selection of the most sustainable alternatives needs to be based on a number of criteria that need to be recognized and agreed amongst the stakeholders.